2019
DOI: 10.1186/s13104-019-4571-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of poorly controlled asthma among asthmatic patients in Jimma University Medical Center, Southwest Ethiopia: a case control study

Abstract: Objective The aim of this study was to assess determinants of poorly controlled asthma among asthmatic patients on follow up at Jimma University Medical Center, Southwest Ethiopia. A facility based case control study involving chart review and patient interview was conducted from April 01/2017 to May 30/2017. Consecutive sampling method was used to select 121 cases and 121 controls. Descriptive statistics were used to present socio demographic data and drug prescription pattern while logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…This nding is in line with studies conducted in China (33), UK (40), North African and Middle East countries (41), Morocco (35), and Nigeria (18). A previous study conducted at Jimma Medical Center, Ethiopia, also showed that the odds of uncontrolled asthma was about 8.5 times higher among nonadherent patients when compared to the adherent ones (24). The possible explanation for this might be a rapid decline in lung function as a result of non-adherence to medications (42).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This nding is in line with studies conducted in China (33), UK (40), North African and Middle East countries (41), Morocco (35), and Nigeria (18). A previous study conducted at Jimma Medical Center, Ethiopia, also showed that the odds of uncontrolled asthma was about 8.5 times higher among nonadherent patients when compared to the adherent ones (24). The possible explanation for this might be a rapid decline in lung function as a result of non-adherence to medications (42).…”
Section: Discussionsupporting
confidence: 90%
“…The fact that adequate control was not achieved in a signi cant proportion of asthmatic patients, despite the presence of effective medications, emphasizes the importance of identifying the determinants of uncontrolled asthma. Even though a couple of studies have been conducted in Ethiopia (12)(13)(14)24), majority of them were cross-sectional in nature focusing mainly on socio-demographic, clinical, and some behavioral factors. The studies didn't give attention to housing factors, which play a major role in asthma control as the cases pass most of their time in the home environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been published on the prevalence and associated factors of non-adherence to inhaled medications among adult asthmatic patients in Ethiopia [18][19][20][21][22][23], the general prevalence remains unknown. Therefore, the primary purpose of this systematic review and meta-analysis is to determine the pooled national prevalence of non-adherence to inhaled medications among adult asthmatic patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Self-perceived poor asthma control was associated with any activity limitation due to asthma and inconsistent inhaled corticosteroid use [23]. Lack of health education on metered-dose inhaler technique [AOR = 4.96; 95% CI (1.08-22.89)] [29].…”
Section: Discussionmentioning
confidence: 99%